Israel Studies Forum (JSTOR)
The Israel Studies Review (ISR) is the journal of the Association for Israel Studies, an international and interdisciplinary scholarly organization dedicated to the study of all aspects of Israeli society, history, politics, and culture. ISR explores modern and contemporary Israel from the perspective of the social sciences, history, the humanities, and cultural studies and welcomes submissions on these subjects.
Keywords: Jewish Studies